Tales of Terror - Poe, Edgar Allan (United Kingdom Cambridge University Press, 2009)
The heart of a dead man won't stop beating; a girl's strange new employer holds a dark secret; a tree hides something terrible; body-snatchers encounter a surprise; a woman is obsessed by a man that only she can see; a rich man shows his poor cousin his dangerous Brazilian cat and many more!
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Language Learning; Reading books; Lower-intermediate Level; Fiction; Horror